2002
DOI: 10.1046/j.1532-5415.2002.50611.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Using Mini Nutritional Assessment and Subjective Global Assessment Predict Mortality in Geriatric Patients

Abstract: Fewer than one-third of newly admitted geriatric patients had a normal nutritional status according to SGA and MNA. BMI, arm anthropometry, body fat mass, and handgrip strength were reduced, and 1-, 2-, and 3-year mortality was higher in patients classified as malnourished. The present data justify the use of SGA and MNA for the assessment of nutritional status in geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
173
2
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(198 citation statements)
references
References 28 publications
13
173
2
10
Order By: Relevance
“…The relationship between low BMI and higher mortality may be explained by lower fat free mass in thin individuals rather than overall leanness 28 . Low BMI and weight loss be a proxy for malnutrition, which is common in sick elderly persons 36 . Low BMI and low body cell mass are predictors of higher mortality in nursing home residents 37 , and in hospitalized elderly after discharge 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between low BMI and higher mortality may be explained by lower fat free mass in thin individuals rather than overall leanness 28 . Low BMI and weight loss be a proxy for malnutrition, which is common in sick elderly persons 36 . Low BMI and low body cell mass are predictors of higher mortality in nursing home residents 37 , and in hospitalized elderly after discharge 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with osteoporotic hip fractures have previously been found to be undernourished and suffering from proteinenergy malnutrition (PEM) (Ponzer et al, 1999). Osteoporosis is also a predictor of mortality (Johnell et al, 2004) and, likewise, the MNA has been found to predict mortality in geriatric patients both during short-term stays in the hospital (Van Nes et al, 2001) and during a long-term 3-year followup (Persson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The Mini-Nutritional Assessment (MNA), a test developed to determine the risk of malnutrition in older people (Guigoz et al, 1996), has been employed to detect nutritional deficiencies in institutional settings (Saletti et al, 2000) as well as in healthy general populations (Scheirlinckx et al, 1999). Moreover, this test has been found to predict mortality in geriatric patients (Persson et al, 2002) and in both an elderly Danish population and among free-living elderly Swedish subjects receiving public services and care (Beck et al, 2001;Saletti et al, 2005). In a comparison of ultrasound measurements of the calcaneus with MNA test scores in a population of institutionalized elderly women, Gerber et al (2003) observed no correlation at all between the MNA score and the ultrasound parameter Speed of Sound (SOS) and only a weak trend towards a correlation with the Broadband Ultrasound Attenuation (BUA).…”
Section: Introductionmentioning
confidence: 99%
“…The patient-generated SGA (PG-SGA) is a further modification of the SGA and has been specifically developed for patients with cancer (Ottery, 1996). The PG-SGA has been used for nutritional assessment in patients with various types of cancer such as cancer of the oesophagus, stomach, pancreas, lung, colorectum, breast and head and neck (Bauer et al, 2002;Persson et al, 2002;Isenring et al, 2003;Ravasco et al, 2003Ravasco et al, , 2005Bauer and Capra, 2005;Desbrow et al, 2005;Horsley et al, 2005;Segura et al, 2005). Bauer et al (2002) compared the scored PG-SGA with the SGA for patients with cancer and suggested the PG-SGA be used for further studies to detect malnutrition in cancer populations.…”
Section: Introductionmentioning
confidence: 99%